2020
DOI: 10.3389/fcell.2020.00315
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced VEGF/VEGF-R and RUNX2 Expression in Human Periodontal Ligament Stem Cells Cultured on Sandblasted/Etched Titanium Disk

Abstract: Bone formation, in skeletal development or in osseointegration processes, is the result of interaction between angiogenesis and osteogenesis. To establish osseointegration, cells must attach to the implant in a direct way without any deposition of soft tissue. Structural design and surface topography of dental implants enhance the cell attachment and can affect the biological response. The aim of the study was to evaluate the cytocompatibility, osteogenic and angiogenic markers involved in bone differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…hPDLSCs have osteogenic, adipogenic, and chondrogenic differentiation potential [ 50 ]; they have been demonstrated to proliferate and show signs of osteogenic differentiation on titanium surfaces [ 51 ]. A previous study by Marconi et al confirmed the present findings that surface treatment did not have an essential impact on the morphology of hPDLSCs grown on titanium surfaces [ 52 ]; however the study did not investigate plastic control. According to the present study, a lower Col1 gene expression in hPDLSCs after 120 h was detected on the MP-coated surface compared to the reference samples, which could also hint at reduced osteogenesis under in vitro conditions.…”
Section: Discussionsupporting
confidence: 85%
“…hPDLSCs have osteogenic, adipogenic, and chondrogenic differentiation potential [ 50 ]; they have been demonstrated to proliferate and show signs of osteogenic differentiation on titanium surfaces [ 51 ]. A previous study by Marconi et al confirmed the present findings that surface treatment did not have an essential impact on the morphology of hPDLSCs grown on titanium surfaces [ 52 ]; however the study did not investigate plastic control. According to the present study, a lower Col1 gene expression in hPDLSCs after 120 h was detected on the MP-coated surface compared to the reference samples, which could also hint at reduced osteogenesis under in vitro conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Among oral stem cells, hPDLSCs are characterized by multipotency and highly proliferative potential [ 13 ]. hPDLSCs have shown a potential angiogenic role dependent on the vascular endothelial growth factor (VEGF), which plays a key role in the implant osseointegration [ 14 ]. It is well known that a good osseointegration needs to be supported by the formation of new bone tissue, which is allowed by a good supply of nourishment and oxygen through the vessels [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that for optimal bone remodeling, the different effects of constructs on oseoclastogenesis also need to be considered and may also differ per skeletal site. Knowledge of local cells, such as the stem cells of the oral cavity [ 12 ], will ultimately lead to the better healing and osseointegration of implants [ 13 ].…”
Section: Introductionmentioning
confidence: 99%